Public-Private-Community Partnerships in Management and Delivery of Water to Urban Poor: The Case of Metro Manila - Cristina C. David; Arlene B. Inocencio (Philippine Institute for Development Studies (PIDS), 2001)
In the Philippines, the Public-Private-Community Partnerships (PPCPs) are serving the poor with water through public faucets, group taps, bulk water, and individual connections. The removal of technical and institutional barriers in providing water in urban poor communities or informal settlements in Metro Manila has allowed delivery of different forms of water services in these areas. This delivery of service results in benefits to the poor which include access to and availability of safe and better quality water, much reduced cost to households, increased per capita consumption contributing to better health and sanitation, and freed-up time which households now use for more childcare, income earning activities, and even more leisure. The principal partners in this PPCPs are the government as represented by the residual water utility and the regulatory office as well as the local government, the private sector as represented by the two private concessionaires of the water utility, and the local associations and nongovernment organizations. Participation of the different parties ranged from small, informal and immediate as in the contribution of labor or mobilization of a community, or capability building and empowering of a community, to more substantial, formal and continuing such as the concession agreement between the water utility and the private concessionaires, the management of a mini water distribution system or a billing and collection contract. There are indications and good reasons to believe that provision of water for the poor and poor communities can be a potent tool for alleviating poverty as it impacts on health, income and consumption, and gender and social inclusion. In this sense, the PPCPs which are delivering water to the poor are contributing to poverty alleviation. The valuable lessons learned in the case of Metro Manila maybe operationalized and improved to comprise good practices applicable to other water utilities in other areas.
Keywords: 330; urban poor; private sector participation; public-private-community partnership; water services; MWSS privatization; public faucets; group taps; bulk water; Wasserversorgung; Wasserpolitik; Städtische Armut; Öffentlich-private Partnerschaft; Manila